Patient-reported activities after bilateral reverse total shoulder arthoplasties - Andrew T Assenmacher; Eduard Alentorn-Geli; Jessica Aronowitz; Matthew Kergosien; Cathy D Schleck; Joaquín Sánchez-Sotelo; Robert H Cofield; John W Sperling (Journal of Orthopaedic Surgery, 2018)
Purpose: Reverse shoulder arthroplasty (RSA) improves pain and function with very good satisfaction. Concerns exist about some activities of daily living (ADLs) involving internal rotation. The purpose of this study was to report how patients with bilateral RSA perform various ADLs. Methods: Thirty-one primary bilateral RSA patients (average age 76 years; 21 women and 10 men) completed a survey to assess various outcomes. The average time between the second arthroplasty and the survey was 2.7 years (range 1.0–7.8 years). Results: All clinical parameters were favorable. All patients reported being able to easily manage toileting and 87% reaching their back pocket. However, 29% found difficulty and 39% were unable to wash their back or put on bra. In comparison with various unilateral arthroplasty types, there was no statistical difference in overall activities ( p < 0.05). Conclusion: Bilateral RSA can provide good functional outcome and high satisfaction. Patients manage most ADLs easily with some limitations in activities requiring extreme internal rotation.